Antimicrobial peptide KR-32 alleviates Escherichia coli K88–induced fatty acid malabsorption by improving expression of fatty acid transporter protein 4 (FATP4)1. (8th April 2019) - Liu, Heyuan; Cao, Xiaoxuan; Wang, Hong; Zhao, Jian; Wang, Xinxia; Wang, Yizhen
Abstract: Bacterial infection causes nutrient malabsorption in small intestine. KR-32, a kind of synthetic antimicrobial peptide, has the bacteriostatic effect. In the present study, 2 experiments were designed to analyze the effects of KR-32 on fat absorption of piglets with or without Escherichia coli infection. In Exp. 1, 12 weaning piglets (21 d old) were allocated to 2 groups: piglets with an intraperitoneal (i.p. ) injection of antimicrobial peptide KR-32 (APK ) and piglets with an i.p. injection of an equivalent volume (1 mL) of phosphate-buffered saline (PBS) (CON-1). Results showed that after 7 d of growth, KR-32 did not significantly change growth performance and apparent total tract digestibility (ATTD ) of feed nutrients of normal pigs. To confirm whether KR-32 affects those of enterotoxigenic Escherichia coli (ETEC ) K88–challenged pigs, we performed Exp. 2, in which 18 piglets (28 d old) were divided into the following 3 groups: 1) piglets orally challenged with 1 × 10 10 cfu ETEC K88 on day 1 followed by an i.p. injection of 0.6 mg/kg KR-32 (K88 + APK); 2) piglets orally challenged with 1 × 10 10 cfu ETEC K88 on day 1 followed by an i.p. injection of an equivalent volume (1 mL) of PBS (K88); and 3) piglets with an oral administration of fresh Luria–Bertani broth (50 mL) followed by an i.p. injection of an equivalent volume of PBS (CON-2). Results showed that ETEC K88 challenge led to poor ADFI, ADG, and G:F in piglets; decreased ATTD of feed nutrients, especially CP and ether extract (EE ); and intestinal morphology disorder. After i.p. injection of KR-32, ADG and ATTD of CP and EE were greatly increased, G:F was significantly reduced ( P < 0.05), and, especially, ATTD of EE returned to a normal level compared with group CON-2. Fatty acid absorption also highly increased after KR-32 injection. Then we focused on fat digestion and fatty acid uptake. The pH in the intestine and pancreas lipase showed no difference among the 3 treatment groups, whereas fatty acid transporter protein 4 (FATP4 ) expression was remarkably improved ( P < 0.05) and the epithelial barrier was recovered after i.p. injection of KR-32. In conclusion, KR-32, given to ETEC K88–challenged piglets, improved growth performance, ATTD of EE, fatty acid absorption, and intestinal morphology, which indicated that KR-32 was likely to improve the expression of FATP4 and by repairing the epithelial barrier, thereby alleviating fatty acid malabsorption.